"Is There a Course Where we Learn How to Interact with Kids?": Readying Couple and Family Therapy Students for Practice with Youth. Issue 2 (15th March 2023) - Heiden-Rootes, Katie M.; Zubatsky, Max; Meyer, Dixie; Secrest, Scott
Abstract: Family relationships are protective against poor behavioral health for youth. Couple and Family Therapy (CFT) graduate programs are critical for readying the behavioral workforce to work systemically with youth and their families. This study identified the elements of a CFT masters training process that readied students to work with youth. Qualitative description with focus group interviews of three cohorts of master's students ( n = 14) was used. Thematic analysis identified five themes demonstrating the primacy of early experiences for fostering safety, reflective and active training approaches, multicultural and sexuality topics, and pragmatics of talking to physicians and children.